2005
DOI: 10.1177/154405910508401009
|View full text |Cite
|
Sign up to set email alerts
|

Possible Link between Glycolysis and Apoptosis Induced by Sodium Fluoride

Abstract: Fluoride has been used to prevent caries in the dentition, but the possible underlying mechanisms of cytotoxicity induction by this compound are still unclear. Since fluoride is known as an inhibitor of glycolytic enzymes, we investigated the possible connection between NaF-induced apoptosis and glycolysis in human promyelocytic leukemia HL-60 cells. NaF-induced apoptotic cell death is characterized by caspase activation, internucleosomal DNA fragmentation, loss of mitochondrial membrane potential, and product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 16 publications
(18 reference statements)
5
22
1
4
Order By: Relevance
“…However, 3-BrPA failed to induce Akt phosphorylation in HeLa cells, suggesting that the inhibition of hexokinase or the depletion of intracellular ATP concentration is not related to 2-DG-induced Akt phosphorylation. We also targeted other enzymes in the glycolytic pathways by inhibiting 6-phospho-D-gluconate:NADP oxidoreductase (6-PG dehydrogenase) with 6-aminonicotinamide (36), pyruvate dehydrogenase with arsenic (37), lactate dehydrogenase with sodium oxamate (38), transketolase-like-1 with oxythiamine, and enolase with sodium fluoride (39), yet most of them did not induce Akt phosphorylation, suggesting that the inhibition of glycolysis is not linked to Akt activation.…”
Section: Discussionmentioning
confidence: 99%
“…However, 3-BrPA failed to induce Akt phosphorylation in HeLa cells, suggesting that the inhibition of hexokinase or the depletion of intracellular ATP concentration is not related to 2-DG-induced Akt phosphorylation. We also targeted other enzymes in the glycolytic pathways by inhibiting 6-phospho-D-gluconate:NADP oxidoreductase (6-PG dehydrogenase) with 6-aminonicotinamide (36), pyruvate dehydrogenase with arsenic (37), lactate dehydrogenase with sodium oxamate (38), transketolase-like-1 with oxythiamine, and enolase with sodium fluoride (39), yet most of them did not induce Akt phosphorylation, suggesting that the inhibition of glycolysis is not linked to Akt activation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an exposure of the human promyelocytic HL-60 cells to 2-5 mM NaF led to significant increase in the level of cytosolic cytochrome c, activation of caspase-3, and subsequent cleavage of intact PARP leading to DNA damage [45,46,129]. In the same cells, Otsuki et al [47] reported an increased activity of caspase-9. The similar activation of caspase-3, cleavage of PARP, and DNA fragmentation were observed in the MDPC-23 odontoblast-like cells exposed to 5mM NaF [21].…”
Section: Caspasesmentioning
confidence: 97%
“…Many of these cellular events ultimately lead to cell death. NaFinduced apoptosis was demonstrated in the cells from different organs and tissues including lungs [25,26], kidneys [27,28], liver [29][30][31], brain [32][33][34], pancreas [35,36], thymus [37], endometrium [38,39], bone marrow [40], hair follicles [41], erythrocytes [42][43][44], as well as leukemic cells [45][46][47].…”
Section: Fluoride-induced Toxicity and Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, uoride has shown considerably higher cytotoxicity against tumor cell lines than normal cells [36]. Besides, in this study, just high concentration of the prepared samples is investigated which may result in di erent observation than concentrations lower than 1% of sample test.…”
Section: Antibacterial Assessmentmentioning
confidence: 99%